2015
DOI: 10.1155/2016/7463407
|View full text |Cite
|
Sign up to set email alerts
|

The Responses of Tissues from the Brain, Heart, Kidney, and Liver to Resuscitation following Prolonged Cardiac Arrest by Examining Mitochondrial Respiration in Rats

Abstract: Cardiac arrest induces whole-body ischemia, which causes damage to multiple organs. Understanding how each organ responds to ischemia/reperfusion is important to develop better resuscitation strategies. Because direct measurement of organ function is not practicable in most animal models, we attempt to use mitochondrial respiration to test efficacy of resuscitation on the brain, heart, kidney, and liver following prolonged cardiac arrest. Male Sprague-Dawley rats are subjected to asphyxia-induced cardiac arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…Using the CA+CPB model, we previously found that rats did not show any measurable brain function after 30 min of CA and 60 min of CPB, but maintained adequate heart and kidney function (Kim et al, 2014). Consistent with the physiological outcomes, the decrease in mitochondrial state-3 respiration was significantly greater in the brain than other tissues in these resuscitated animals (Kim et al, 2016). This correlation between physiological outcome and mitochondrial respiration activity prompted our current exploration of the mitochondrial ETC for molecular mechanisms of ischemia/reperfusion injury in the brain.…”
Section: Introductionsupporting
confidence: 62%
“…Using the CA+CPB model, we previously found that rats did not show any measurable brain function after 30 min of CA and 60 min of CPB, but maintained adequate heart and kidney function (Kim et al, 2014). Consistent with the physiological outcomes, the decrease in mitochondrial state-3 respiration was significantly greater in the brain than other tissues in these resuscitated animals (Kim et al, 2016). This correlation between physiological outcome and mitochondrial respiration activity prompted our current exploration of the mitochondrial ETC for molecular mechanisms of ischemia/reperfusion injury in the brain.…”
Section: Introductionsupporting
confidence: 62%
“…Alterations in mitochondrial function have been detected in a variety of CA models in a variety of animal species 22, 24, 48. Postischemic conditioning has been shown to improve survival in swine resuscitated from CA 49.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the central role of VO 2 and CO 2 production (VCO 2 ) in mitochondrial energy metabolism, and the evidence that mitochondrial function is altered after resuscitation from CA,22, 23, 24 we hypothesize that the metabolic injury sustained by resuscitated animals will manifest as alterations in systemic VO 2 and VCO 2 . While ex vivo results suggest that VO 2 will decrease, we have purposefully left our hypothesis open because the conditions used in ex vivo experimentation do not reflect the postresuscitation cellular milieu.…”
Section: Introductionmentioning
confidence: 99%
“…34 Dysfunction of the metabolism in glycolysis (the Krebs cycle) and the ornithine cycle involve the same issue: mitochondria dysfunction in cardiac arrest, which is well studied in animal models. 35,36 An animal model paradigm, however, regardless of how well it is studied, is not the same as the in vivo metabolism of these molecules in humans. Lactate does have a large network that shuttles and metabolizes it everywhere.…”
Section: Discussionmentioning
confidence: 99%